(untitled) (Journal of Hama University, 2022)
Introduction: the use of conventional complete dentures in prosthesis for edentulous patients is considered to have acceptable results for most patients, despite some defects in the method of its manufacture, as a result, the computer technique (CAD/CAM) came to overcome most of these disadvantages. Aim of the Study: The aim of this study is to investigate the possibility of using the computer technique (CAD/CAM) in the manufacture of bases of maxillary complete dentures, and its impact on the retention of complete dentures. Materials and Methods: The sample included 12 edentulous patients, ranging in age between 52-66 years (6 male and 6 female). For each patient, two maxillary complete dentures were made, one by conventional method, and the other its base was made by the computer method (CAD/CAM), by milling [PMMA] blocks, then the rest of the stages were completed by the conventional method. Then, the retention of the maxillary complete denture was measured (in Newton) for each maxillary complete denture by using an electronic retention measurement device (the spring). The data obtained was statistically analyzed using Student’s independent T-test. The level of confidence was set at 95%. Results: There was statistically significant difference in the average mean values of the retention of the maxillary complete dentures with bases manufactured with (CAD/CAM) and conventional maxillary complete dentures in research sample at significance level much smaller than the value 0.05. (P-value=0.000). Conclusions: The results showed that the use of computer methods in manufacturing of complete dentures contributes in increasing the retention of the maxillary complete dentures